Relatório de Estágio Profissional "DA SUPERAÇÃO DE OBSTÁCULOS À SUPERAÇÃO DE EXPECTATIVAS" - Sara Filipa Lopes de Sousa (2017)
It was within the scope of the Professional Internship integrated in the second year of the 2nd Cycle in Physical Education Teaching in Basic Education, in the Faculty of Sport in the University of Porto in the year of 2016/2017 that this essay was prepared. The Internship presents itself as the culmination of the academic formation, thus ensuring that the student puts into practice all the knowledge that has been acquired over the years. This document is organized by different chapters: in the first one the "Introduction", where a brief characterization of the Professional Stage was realized; the second one is the "Personal Framework", where my expectations are shared and all my journey till here, the third is the "Institutional Framework", where I characterize the stage, the environment where it was realized and I also present the Internship Center that I accompanied, without forgetting the classes that I teach. The fourth, the "Operational Framework", which is divided into three areas. Area 1 - Organization and Management of Teaching and Learning, reflected on the conception, planning, realization and evaluation of teaching. Area 2 - Participation in school and Relations with the Community, where all the activities in which I got involved during the school year are referenced. Area 3 - Professional Development, is related to the research-action process developed by me regarding the effect of Functional Training in my class. The fifth chapter, presents a brief reflection of the whole course of the Professional Internship. And finally, the sixth chapter contemplates the bibliographical references that were used.